A Novel Murine Model for the In Vivo Study of Transdermal Drug Penetration - Gábor Eros; Petra Hartmann; Szilvia Berkó; Eszter Csizmazia; Erzsébet Csányi; Anita Sztojkov-Ivanov; István Németh; Piroska Szabó-Révész; István Zupkó; Lajos Kemény (The Scientific World Journal)
Enhancement of the transdermal penetration of different active agents is an important research goal. Our aim was to establish a novel in vivo experimental model which provides a possibility for exact measurement of the quantity of penetrated drug. The experiments were performed on SKH-1 hairless mice. A skin fold in the dorsal region was fixed with two fenestrated titanium plates. A circular wound was made on one side of the skin fold. A metal cylinder with phosphate buffer was fixed into the window of the titanium plate. The concentration of penetrated drug was measured in the buffer. The skin fold was morphologically intact and had a healthy microcirculation. The drug appeared in the acceptor buffer after 30 min, and its concentration exhibited a continuous increase. The presence of ibuprofen was also detected in the plasma. In conclusion, this model allows an exact in vivo study of drug penetration and absorption.